Eating Disorders within the Dental Practice: A Literature Review (Global Journal of Medical Research, 2016)
Eating Disorders (ED) affect a great deal of individuals around the world, yet initial diagnosis continues to be elusive to detect. Many of the physical and psychological manifestations that occur in patients suffering from an ED can be seen by both medical and dental professionals; however the mentality behind this diagnosis is complex. The task of discussing the disorder with the patient has a tendency to be passed amongst practitioners even though current literature agrees that early diagnosis is key to prevention and successful treatment. Two areas of focus that need to be addressed are who is responsible for making the initial diagnosis and what needs to be included for prevention and/or successful treatment.
Keywords: eating disorder; anorexia; bulimia; bing-eating disorder; dentistry; prevention